HUBUNGAN ANTARA PENGETAHUAN DAN MEDIA PORNOGRAFI DENGAN PERILAKU SEKS DI SMA BAKTI IBU 8 PALEMBANG TAHUN 2011 - Leny Leny (STIKes Budi Mulia Sriwijaya, 2012)
ABSTRACT Adolescence is a period of transition from the early days of children up to early adulthood, which entered at the age of about 10 to 12 years and ended at the age of 18 years to 22 years. The purpose of this study was to determine the relationship between knowledge and media pornography to sexual behavior of students / Senior high school Bakti Ibu 8 Palembang in 2011. The design of this study using the analytic survey using cross sectional approach using random sampling method. In a proportional stratified random sampling technique in which the variables studied were the independent variables (knowledge and pornographic media) and independent variables (sexual behavior). Samples in this study were part of students / class XI student in Senior high school Bakti Ibu 8 Palembang 2011 that totaled 150 students. These results indicate that respondents who had sex as many as 29 people (19.4%) and that did not have sex as many as 121 people (80.6%), good knowledge of the respondents as many as 132 people (88%) and lack of knowledge as many as 18 people (12%), respondents pornographic media as much as 9 persons (6.38%) and respondents are not pornographic media 141 people (93.62%). From the results of Chi-Square test statistic found a significant association between knowledge and sexual behavior in adolescents where (p value = 0.006). The study is expected to be the guardians of education by parents of students further enhance the fabric of communication between them in the teenage years watching his protege. ABSTRAK Masa Remaja adalah suatu periode transisi dari masa awal anak-anak hingga masa awal dewasa, yang dimasuki pada usia kira-kira 10 hingga 12 tahun dan berakhir pada usia 18 tahun hingga 22 tahun. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan media pornografi dengan perilaku seksual siswa/siswi SMA Bakti Ibu 8 Palembang tahun 2011. Desain penelitian ini menggunakan survey analitik dengan menggunakan pendekatan cross sectional dengan menggunakan metode random sampling. Dalam teknik stratified proporsional random sampling dimana variabel yang diteliti adalah variabel independen (pengetahuan dan media pornografi) dan variabel independen (perilaku seks). Sampel pada penelitian ini adalah sebagian siswa/siswi kelas XI di SMA Bakti Ibu 8 Palembang Tahun 2011 yang berjumlah 150 siswa. Hasil penelitian ini menunjukkan bahwa responden yang melakukan seks sebanyak 29 orang (19,4%) dan yang tidak melakukan seks sebanyak 121 orang (80,6%), responden pengetahuan baik sebanyak 132 orang (88%) dan pengetahuan kurang sebanyak 18 orang (12%), responden media pornografi sebanyak 9 orang (6,38%) dan responden tidak media pornografi 141 orang (93,62%). Dari hasil uji statistik Chi-Square didapatkan adanya hubungan yang bermakna antara pengetahuan dan perilaku seks pada remaja dimana (p value =0,006). Penelitian ini diharapkan agar pihak pendidikan dengan orang tua wali murid lebih meningkatkan lagi jalinan komunikasi antar mereka dalam mengawasi masa-masa remaja anak didiknya.